Visual methodologies, sand and psychoanalysis: employing creative participatory techniques to explore the educational experiences of mature students and children in care. Issue 4 (2nd October 2017) - Mannay, Dawn; Staples, Eleanor; Edwards, Victoria
Abstract : Social science research has witnessed an increasing move towards visual methods of data production. However, some visual techniques remain pariah sites because of their association with psychoanalysis; and a reluctance to engage with psychoanalytically informed approaches outside of therapy-based settings. This paper introduces the method of 'sandboxing', which was developed from the psychoanalytical approach of the 'world technique'. 'Sandboxing' provides an opportunity for participants to create three-dimensional scenes in sand-trays, employing miniature figures and everyday objects. Data are presented from two studies conducted in Wales, UK. The first, exploring mature students' accounts of higher education, and the second, exploring the educational experiences of children and young people in public care. The paper argues that psychoanalytical work can be adapted to enable a distinctive, valuable and ethical tool of qualitative inquiry; and illustrates how 'sandboxing' engendered opportunities to fight familiarity, enabled participatory frameworks, and contributed to informed policy and practice.